Comparative Genomics of Mycoplasma synoviae and New Targets for Molecular Diagnostics - Xu, Bin; Chen, Xi; Lu, Fengying; Sun, Yu; Sun, Huawei; Zhang, Jingfeng; Shen, Liya; Pan, Qunxing; Liu, Chuanmin; Zhang, Xiaofei (Frontiers in Veterinary Science, 2021)
Mycoplasma synoviae is an important pathogen of poultry, causing significant economic losses in this industry. Analysis of the unique genes and shared genes among different M. synoviae strains and among related species is helpful for studying the molecular pathogenesis of M. synoviae and provides valuable molecular diagnostic targets to facilitate the identification of M. synoviae species. We selected a total of 46 strains, including six M. synoviae strains, from 25 major animal (including avian) Mycoplasma species/subspecies that had complete genome sequences and annotation information published in GenBank, and used them for comparative genomic analysis. After analysis, 16 common genes were found in the 46 strains. Thirteen single-copy core genes and the 16s rRNA genes were used for genetic evolutionary analysis. M. synoviae was found to have a distant evolutionary relationship not only with other arthritis-causing mycoplasmas, but also with another major avian pathogen, Mycoplasma gallisepticum, that shares the major virulence factor vlhA with M. synoviae. Subsequently, six unique coding genes were identified as shared among these M. synoviae strains that are absent in other species with published genome sequences. Two of the genes were found to be located in the genetically stable regions of the genomes of M. synoviae and were determined to be present in all M. synoviae isolated strains (n=20) and M. synoviae-positive clinical samples (n=48) preserved in our laboratory. These two genes were used as molecular diagnostic targets for which SYBR green quantitative PCR detection methods were designed. The two quantitative PCR methods exhibited good reproducibility and high specificity when tested on positive plasmid controls and genomic DNA extracted from different M. synoviae strains, other major avian pathogenic bacteria/mycoplasmas, and low pathogenic Mycoplasma species. The detection limit for the two genes was 10 copies or less per reaction. The clinical sensitivity and specificity of the quantitative PCR methods were both 100% based on testing chicken hock joint samples with positive or negative M. synoviae infection. This research provides a foundation for the study of species-specific differences and molecular diagnosis of M. synoviae.